Akibat Hukum Perceraian Pernikahan Yang Diisbatkan Terhadap Hak Asuh Anak Menurut Hukum Islam (KHI) Dan Undang-Undang Perkawinan - Muhammad Yusril Alawi; Wiwiek Wahyuningsih (Private Law, 2022)
This research aims to find out legal consequences of divorce in isbat marriage according to Islamic law compilation and Marriage Law and to know the custody after divorce in isbat marriage. The method of this research is normative legal research. Data analytical technique that has been used in this research is qualitative. The result of this research shows that legal consequences of divorce in isbat marriage are former husband or wife that must look after and educate their children, having right to share the property and inheritance. On the other hand, the custodian to the children before adult (mumayyiz) is in their mother and after adult the children have right to choose their custodian.